Producing and marketing made in Ghana goods in the face of trade liberalisation: a case study into selected clothing and footwear industries - Amonoo, Evelyn (2012)
A thesis submitted to the Department of Industrial Management,Kwame Nkrumah University of Science and Technology Kumasi, in partial fulfillment of the requirement of the award of M.A Degree in Industrial Management.